Education Equality and Its Influencing Factors for Migrant Children in the Compulsory Education Stage Based on Multi-Source Data: A Case Study of Dalian, China - Zhang, Zhenchao; Luan, Weixin; Tian, Chuang; Su, Min; Li, Zeyang (Frontiers in Earth Science, 2022)
Inequality in the admission of migrant children is an important manifestation of inequities at the compulsory education stage in China. Spatial differences in the allocation of educational resources and the factors affecting the number of enrolled migrant children led to the following conclusions: (1) The total number of migrant children in Dalian is growing situationally, with a total increase of 29,223 from 2008 to 2020 (2) the migrant children in Dalian in 2020 are distributed in a spatially uneven manner, with most of them concentrated in the periphery of the Ganjingzi district, south of the Jinzhou area (suburban areas), where very few of them were enrolled in high-quality junior high and primary schools. The distribution of educational resources differed significantly between the central urban areas and suburban area (4) The internal factor of schools constraining the admission of migrant children is the teacher-student ratio. For every 1% increase in the teacher-student ratio, the number of migrant children decreases by 4.12%. The main external factors affecting the admission of migrant children were rental prices and the area occupied by construction, which increased by 1% for each 2000 m buffer range of school and 0.25% for the number of migrant children and decreased by 0.29% for each 2000 m buffer range of the school.